2020
DOI: 10.1002/ppul.25188
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of longitudinal outcomes for children using long‐term noninvasive ventilation

Abstract: Background Noninvasive ventilation (NIV) is a first‐line therapy for sleep‐related breathing disorders and chronic respiratory insufficiency. Evidence about predictors that may impact long‐term NIV outcomes, however, is scarce. The aim of this study is to determine demographic, clinical, and technology‐related predictors of long‐term NIV outcomes. Methods A 10‐year multicentred retrospective review of children started on long‐term continuous or bilevel positive airway pressure (CPAP or BPAP) in Alberta. Demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…During this period, the number of children with CNS disorders treated by NIV/CPAP has been multiplied by 16, from 11 to 182 children 18 . Similar trends have been observed in Canada, Italy, and Spain 23,25–27 …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…During this period, the number of children with CNS disorders treated by NIV/CPAP has been multiplied by 16, from 11 to 182 children 18 . Similar trends have been observed in Canada, Italy, and Spain 23,25–27 …”
Section: Discussionsupporting
confidence: 80%
“…18 Similar trends have been observed in Canada, Italy, and Spain. 23,[25][26][27] Nocturnal gas exchange recordings were the main investigation performed before NIV/CPAP initiation. In 29% of children, it was the sole investigation.…”
Section: Discussionmentioning
confidence: 99%
“…11 We found that obesity was a risk factor for decreased PAP usage over time, similar to a previous 10-year multicentred retrospective review that evaluated longitudinal PAP adherence among 622 children aged 0-18 years old, which showed that children with obesity or metabolic syndrome were more likely to decline PAP therapy (OR =2.077 [95% CI 1.110-3.888]). 39 The reasons for these findings are unclear; however, there is one study suggesting lack of perceived benefits of PAP in this population may contribute to decreased use. 16 Of concern, obesity is an independent risk factor for susceptibility to and severity of COVID-19 which is related to worsening outcomes including increased risk of hospitalization, critical care admission and mortality.…”
Section: Discussionmentioning
confidence: 97%
“…Hip and elbow joints cannot be fully extended, while finger, knee and ankle joints are hyperextended. Because of the reduced size of the chest, breathing is often impaired [18,38,39]. The narrowness of the nasopharynx often causes infections, especially of the upper respiratory tract [18,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the reduced size of the chest, breathing is often impaired [18,38,39]. The narrowness of the nasopharynx often causes infections, especially of the upper respiratory tract [18,38,39]. Middle ear infections may also occur.…”
Section: Introductionmentioning
confidence: 99%